Loss of LAMP5 interneurons drives neuronal network dysfunction in Alzheimer’s disease - Yuanyuan Deng; Mian Bi; Fabien Delerue; Shelley L. Forrest; Gabriella Chan; Julia van der Hoven; Annika van Hummel; Astrid Feiten; Seojin Lee; Iván Martínez-Valbuena; Tim Karl; Gábor G. Kovács; et al. (2022)
In Alzheimer's disease (AD), where amyloid-β (Aβ) and tau deposits in the brain, hyperexcitation of neuronal networks is an underlying disease mechanism, but its cause remains unclear. Here, we used the Collaborative Cross (CC) forward genetics mouse platform to identify modifier genes of neuronal hyperexcitation. We found LAMP5 as a novel regulator of hyperexcitation in mice, critical for the survival of distinct interneuron populations. Interestingly, synaptic LAMP5 was lost in AD brains and LAMP5 interneurons degenerated in different AD mouse models. Genetic reduction of LAMP5 augmented functional deficits and neuronal network hypersynchronicity in both Aβ- and tau-driven AD mouse models. To this end, our work defines the first specific function of LAMP5 interneurons in neuronal network hyperexcitation in AD and dementia with tau pathology.